Rationalizing Pharmaceutical Spending - Garcia-Goni, Manuel (Washington, D.C. : International Monetary Fund, 2022)
Pharmaceutical spending accounts for a large share of health spending worldwide. While pharmaceuticals are an indispensable component of effective modern health systems, and their benefits in terms of increasing life expectancy and improving quality of life are unquestionable, the large variation in pharmaceutical spending across countries suggests that there may be large efficiency gains to be realized. This paper reviews the existing literature and databases on the level and composition of pharmaceutical spending and estimates potential efficiency gains from increased use of generics. It also reviews how countries organize the procurement and tendering of pharmaceuticals and the implications for spending. Finally, the paper identifies the various channels through which spending inefficiencies can arise and identifies reform options for reducing pharmaceutical spending while ensuring quality health outcomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Generics; Health; National Government Expenditures and Related Policies; Pharmaceutical Policy; Pharmaceutical Spending